Condições de decomposição de precursores de fonte única nas propriedades semicondutores à base de sulfetos de bismuto, zinco ou estanho e óxido de estanho - Guilherme Oliveira Siqueira (2013)
Semicondutor materials have a wide range of technological applications due to their physical and chemical properties. Therefore, it is very relevant to understand the influence of the synthetic method used with the properties. In this research, a major contribution was made to the optimization and control of the properties of tin sulfides andoxides as well as zinc and bismuth sulfides. The materials were prepared through thermal and hydrothermal decomposition of single source precursors and the influence of the experimentalconditions on the final properties was also studied. Single source precursors such as [Zn(EDT)2] and [Bi(EDT)3], EDT = dyethildithiocarbamate, and [Sn4But4S6] e [Sn4But4O6],But = ter butyl radicals; were obtained and characterized by thermal analysis. Thermal decomposition of precursors were carried out in a tubular furnace at different temperatures and the solids obtained were identified and characterized by Scanning and Transmissionelectron microscopies and X ray diffraction measurements. The sulphides and oxides were obtained with broad particle/crystals size distribution and it was not possible trough the variation of experimental conditions, to control the particle/crystal sizes. In order to obtainbetter control of the morphology and microstructural particle properties, hydrothermal method was then used. However, this method presents a large number of variables such as temperature, reaction time, effect of surfactant, pH and solvent. Each one of these variableswas studied with the aim to understand their role on the final properties of the obtained products which were characterized by Scanning and Transmission electron microscopies, X ray diffraction, gas adsorption and photocatalytic tests. Particle/crystal size, shape, degree ofagglomeration and crystal lattice defects were very dependent on the experimental conditions of hydrothermal decomposition of precursors. Band gap energies as well as photocatylitic activities (methylene blue dye degradation) showed to be also very dependent on hydrothermal variables.